Diode pumped highly efficient Yb:Lu3Al5O12 ceramic laser - Zhang, J. (2013)
A diode pumped ytterbium-doped lutetium aluminum garnet (Yb:LuAG) ceramic laser is reported for the first time to our knowledge. Using the solid state reactive vacuum sintering technique we have successfully fabricated high optical quality Yb:LuAG ceramics. We show that even with an uncoated Yb:LuAG ceramic sample a maximum output power of 7 W could be achieved under 13 W absorbed pump power, and the laser has a slope efficiency as high as 63%. Considering that Yb:LuAG has higher thermal conductivity than Yb:YAG under heavy doping situation, Yb:LuAG ceramic could be an attractive laser gain medium for the high power solid state lasers applications.